2021
DOI: 10.3390/antiox10040590
|View full text |Cite
|
Sign up to set email alerts
|

New Amides and Phosphoramidates Containing Selenium: Studies on Their Cytotoxicity and Antioxidant Activities in Breast Cancer

Abstract: Breast cancer is a multifactor disease, and many drug combination therapies are applied for its treatment. Selenium derivatives represent a promising potential anti-breast cancer treatment. This study reports the cytotoxic activity of forty-one amides and phosphoramidates containing selenium against five cancer cell lines (MCF-7, CCRF-CEM, HT-29, HTB-54 and PC-3) and two nonmalignant cell lines (184B5 and BEAS-2B). MCF-7 cells were the most sensitive and the selenoamides I.1f and I.2f and the selenium phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Previously, it was shown that selenium compounds have been known to be highly cytotoxic toward a variety of cancer cell lines [ 12 , 19 , 40 , 41 , 42 ]. In this study, we demonstrated that both EDA-71 and E-NS-4 selenium compounds exhibited cytotoxic activity on breast cancer cell lines (MCF-7 and MDA-MB-231), with IC 50 values in terms of low micromolar concentrations (1.4 to 4.52 µM).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, it was shown that selenium compounds have been known to be highly cytotoxic toward a variety of cancer cell lines [ 12 , 19 , 40 , 41 , 42 ]. In this study, we demonstrated that both EDA-71 and E-NS-4 selenium compounds exhibited cytotoxic activity on breast cancer cell lines (MCF-7 and MDA-MB-231), with IC 50 values in terms of low micromolar concentrations (1.4 to 4.52 µM).…”
Section: Discussionmentioning
confidence: 99%
“…High cytotoxic activity can lead to cell death by several significantly different death pathways—apoptosis, entosis, necrosis, necroptosis (regulated necrosis), and autophagy—and the type of cell death depends on the properties of the chemical compound used or the dose applied [ 12 , 16 , 40 , 42 ]. The study by Shigemi et al [ 47 ] showed that Se compounds direct cancer cells mainly to the apoptosis pathway.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations